Determinants of Olympic fencing performance and implications for strength and conditioning training - Turner, A.; James, N.; Dimitriou, L.; Greenhalgh, A.; Moody, J.; Fulcher, D.; Mias, E.; Kilduff, L. (The Journal of Strength and Conditioning Research, 2014)
Fencing is one of only a few sports that have featured at every modern Olympic games. Despite this, there is still much the sport science team does not know regarding competition demands and athlete physical characteristics. This review aims to undertake an analysis of the current literature to identify what is known, and questions that must be answered to optimize athlete support in this context. In summary, fencing is an explosive sport requiring energy production predominately from anaerobic sources. Lunging and change-of-direction speed seem vital to performance, and strength and power qualities underpin this. In the elimination rounds, fencers are likely to accumulate high levels of blood lactate, and so high-intensity interval training is recommended to reduce the intolerance to and the accumulation of hydrogen ions. Injury data report the hamstrings as a muscle group that should be strengthened and address imbalances caused by continuous fencing in an asymmetrical stance.